Analisis Pengaruh Arah Posisi Panel Surya Terhadap Output Daya Pada Sistem Penerangan Rumah - Mohammad Ashrulloh, Mohammad Munib Rosadi, Mochammad Arif Irfa'i (Reaktom : Rekayasa Keteknikan dan Optimasi, 2021)
The solar Panel is an array of solar cells that can convert light energy of the sun into electricity. The intensity of the light and the power output is strongly influenced by the mounting direction of the position of the solar panel. This research has a purpose to analyze the results of the influence of the direction of the position on the power output and efficiency of solar panel module. The research method used is experimental type quantitative research methods. This method is used to determine the effect of independent variables i.e. the direction of the position on the dependent variable i.e. the power output and the efficiency of the solar panel in a state that is controlled. The results of the data obtained from measurements using the instrument of data collection and the calculation formula. This study obtained different average power output results, for the west 46.72 Watt, the north of 50,30 Watt, the east of 36,17 Watt, and the south 35,78 Watt.